Ultrahigh-strength rare earth aluminum alloy, aluminum alloy product and preparation method of aluminum alloy product
By adding zinc, magnesium, copper and other elements to the aluminum alloy, combined with rare earth scandium and zirconium composite microalloyation and three-stage homogenization, the shortcomings in strength and toughness of the existing aluminum alloy baseball bats are solved, and ultra-high strength and high elongation aluminum seamless pipes are achieved to meet the performance needs of high-end baseball bats.
Patent Information
- Application Number
- CN202411869132.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-25
AI Technical Summary
The existing aluminum alloy baseball bats have not yet met the higher requirements of high-end baseball bats in terms of strength, hardness and toughness, which limits the further improvement of the baseball bats' lightweight, hitting performance and structural design.
A super high strength rare earth aluminum alloy is developed. By adding main alloy elements such as zinc, magnesium, copper, etc., and combining rare earth scandium and zirconium composite microalloyation and three-stage homogenization treatment, a uniformly distributed reinforced phase is formed to improve the tensile strength and yield strength of the alloy.
The ultra-high strength of aluminum alloy is achieved, with tensile strength reaching 700~790MPa, yield strength ≥660MPa, and elongation ≥8.0%, meeting the demand of high-end baseball bats for seamless pipe performance.
Smart Images

Figure BDA0005195310060000011 
Figure BDA0005195310060000041 
Figure FDA0005195310050000011
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aluminum alloys, and in particular to an ultra-high-strength rare earth aluminum alloy, an aluminum alloy product and a preparation method thereof. Background Art
[0002] Baseball has attracted the attention and participation of fans around the world with its unique charm and challenge. As the core equipment of baseball, the design, material and performance of baseball bats are directly related to the players' hitting effect and performance in the game. Modern baseball bats are usually made of advanced materials such as aluminum alloy and carbon fiber. These materials not only greatly reduce the weight of the bat, but also significantly improve the elasticity and strength, so that the bat can be controlled faster and more accurately when swinging, while releasing greater hitting energy.
[0003] Aluminum alloy has become the preferred material for high-end baseball bats due to its superior performance, pleasant hearing and comfortable feel. At present, aluminum alloys used for baseball bats are mainly 6-series aluminum alloys and 7-series aluminum alloys, with strengths generally between 300 and 500 MPa. Although the mechanical properties of some aluminum alloys have been improved, they still do not meet the higher requirements of high-end aluminum alloy baseball bats for strength, hardness, toughness and other properties, which limits the further improvement of baseball bats in terms of lightweight, hitting performance, structural design, etc. Therefore, it is of great significance for researchers to develop an ultra-high-strength aluminum alloy for baseball bats. Summary of the invention
[0004] The technical problem solved by the present invention is to provide an ultra-high-strength rare earth aluminum alloy, which has high strength, hardness and toughness and can be suitable for baseball bats.
[0005] In view of this, the present application also provides an ultra-high strength rare earth aluminum alloy, which comprises, by mass percentage:
[0006]
[0007]
[0008] Si≤0.1%;
[0009] Fe≤0.1%;
[0010] Ti≤0.05%;
[0011] The balance is Al.
[0012] Preferably, the content of Cu is 1.7-2.2%; and / or the content of Mg is 2.0-2.4%; and / or the content of Zn is 8.9-9.8%.
[0013] Preferably, the content of Mn is 0.39-0.60%; and / or the content of Zr is 0.08-0.11%; and / or the content of Sc is 0.035-0.060%.
[0014] The present application also provides an aluminum alloy product, which is prepared from the aluminum alloy.
[0015] Preferably, the aluminum alloy product is a seamless tube for a baseball bat.
[0016] The present application also provides a method for preparing the aluminum alloy product, comprising the following steps:
[0017] S1) melting the pure aluminum ingot according to the composition ratio, adding raw copper, raw zinc, raw magnesium and other master alloys, refining the obtained molten metal, and letting it stand;
[0018] S2) sequentially performing online degassing, online filtering and online adding of a grain refiner on the molten metal after standing, and obtaining an ingot after casting;
[0019] S3) subjecting the ingot to a three-stage homogenization treatment, wherein the first stage temperature of the three-stage homogenization treatment is 390-410° C., the second stage temperature is 450-470° C., and the third stage temperature is 470-475° C.;
[0020] S4) extruding the homogenized ingot, and then performing solid solution quenching and aging treatment.
[0021] Preferably, the grain refiner is Al-5Ti-1B wire.
[0022] Preferably, the insulation time of the first stage is 8 to 12 hours, the insulation time of the second stage is 6 to 10 hours, and the insulation time of the third stage is 26 to 30 hours.
[0023] Preferably, the inlet temperature of the extrusion is 410-460°C, the extrusion speed is 0.1-0.5 mm / s, and the outlet temperature of the extrusion is 370-390°C.
[0024] Preferably, the solution temperature of the solution quenching is 470-480°C, the holding time is 2-8h, the water temperature of the quenching is 20-30°C, the temperature of the aging treatment is 100-150°C, and the time is 12-24h.
[0025] The present application provides an ultra-high strength rare earth aluminum alloy, which includes: Cu 1.6-2.4%; Mg 1.8-2.7%; Zn 8.5-10.0%; Mn 0.3-0.7%; Zr 0.07-0.13%; Sc0.02-0.08%; Si≤0.1%; Fe≤0.1%; Ti≤0.05%; the balance is Al. The present application adds zinc, magnesium, copper and other main alloying elements to the aluminum alloy, so that the zinc, magnesium and copper elements can form an η′ strengthening phase, so that the rare earth aluminum alloy obtains ultra-high tensile strength and yield strength.
[0026] Furthermore, the present application also provides a method for preparing an aluminum alloy product, which forms a large amount of uniformly dispersed L12-type Al3 (Sc, Zr) phase through scandium and zirconium composite microalloying and three-stage homogenization treatment, which inhibits recrystallization and ensures that the fibrous extrusion structure of the pipe can be retained after solution treatment, thereby improving the strength and elongation of the alloy; the main alloying elements such as zinc, magnesium and copper in the rare earth aluminum alloy and the subsequent solution and aging treatment promote the precipitation of zinc, magnesium and copper elements from the matrix to form an η′ strengthening phase, so that the rare earth aluminum alloy obtains ultra-high strength; in addition, in the present application, a medium-high temperature and low-speed piercing extrusion process is adopted, and a high-alloyed ultra-high-strength aluminum alloy seamless pipe is successfully prepared by increasing the extrusion temperature and reducing the extrusion speed. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a surface grain structure photograph of the extruded seamless pipe of Example 5 of the present invention;
[0028] Figure 2 This is a photograph of the fibrous extruded grain structure at the core of the extruded seamless pipe of Example 5 of the present invention;
[0029] Figure 3 This is a photograph of the fibrous extruded grain structure at the core of the aged seamless pipe of Example 5 of the present invention;
[0030] Figure 4 This is a photo of the core part of the recrystallized structure of the aged seamless pipe of Comparative Example 1 of the present invention;
[0031] Figure 5 This is a photo of surface cracking of the extruded seamless pipe of Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0032] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0033] In view of the requirements for higher mechanical properties of high-end baseball bats in the prior art, the present application provides an ultra-high strength rare earth aluminum alloy, which introduces a large amount of main alloying elements such as zinc, magnesium, and copper, matches scandium and zirconium microalloying elements, and combines appropriate preparation processes to make the aluminum alloy have higher strength and elongation, which can meet the performance requirements of seamless pipes for high-end baseball bats. Specifically, the embodiment of the present invention discloses an ultra-high strength rare earth aluminum alloy, which, in terms of mass percentage, includes:
[0034]
[0035] Si≤0.1%;
[0036] Fe≤0.1%;
[0037] Ti≤0.05%;
[0038] The balance is Al.
[0039] In the super-strong rare earth aluminum alloy provided in the present application, the content of Cu is 1.6-2.4%, specifically, the content of Cu is 1.7-2.2%, and more specifically, the content of Cu is 1.8-2.1%. For example, the content of Cu in the present application is 1.72%, 1.74%, 1.80%, 1.85%, 1.92%, 1.95%, 2.01%, 2.04%, 2.06%, 2.12%, 2.16%, 2.20%, 2.28%, 2.30%, 2.36%.
[0040] The content of Mg is 1.8-2.7%, specifically, the content of Mg is 2.0-2.4%, and more specifically, the content of Mg is 2.1-2.3%. For example, the content of Mg in the present application is 1.85%, 1.88%, 1.90%, 1.92%, 2.01%, 2.03%, 2.08%, 2.12%, 2.18%, 2.20%, 2.21%, 2.26%, 2.29%, 2.40%, 2.46%, 2.49%, 2.53%, 2.65%, 2.67%, 2.69%.
[0041] The content of Zn is 8.5-10.0%, specifically, the content of Zn is 8.9-9.8%, and more specifically, the content of Zn is 9.0-9.5%. For example, the content of Zn in the present application is 8.56%, 8.59%, 8.60%, 8.61%, 8.67%, 8.73%, 8.78%, 8.86%, 8.89%, 8.93%, 8.94%, 9.02%, 9.08%, 9.15%, 9.19%, 9.20%, 9.26%, 9.35%, 9.37%, 9.43%, 9.47%, 9.50%, 9.60%, 9.62%, 9.71%, 9.72%, 9.84%, 9.89%, 9.95%, 9.97%.
[0042] The content of Mn is 0.3-0.7%, specifically, the content of Mn is 0.39-0.60%, more specifically, the content of Mn is 0.42-0.56%. For example, the content of Mn in this application is 0.33%, 0.27%, 0.43%, 0.40%, 0.41%, 0.52%, 0.56%, 0.59%, 0.63%, 0.68%.
[0043] The Zr content is 0.07 to 0.13%, specifically, the Zr content is 0.08 to 0.11%, and more specifically, the Zr content is 0.09 to 0.10%.
[0044] The content of Sc is 0.02-0.08%, specifically, the content of Sc is 0.035-0.060%, and more specifically, the content of Sc is 0.040-0.053%. For example, the content of Sc in the present application is 0.021%, 0.026%, 0.028%, 0.031%, 0.033%, 0.037%, 0.038%, 0.042%, 0.041%, 0.040%, 0.048%, 0.051%, 0.052%, 0.055%, 0.059%, 0.063%, 0.063%, 0.068%, 0.072%, 0.075%, 0.078%.
[0045] Fe≤0.1%, specifically, Fe≤0.090%, more specifically, Fe≤0.078%.
[0046] Si≤0.1%, specifically, Si≤0.040%, more specifically, Si≤0.030%.
[0047] Ti≤0.05%, specifically, Ti≤0.03%.
[0048] The present application also provides an aluminum alloy product, which is prepared from the aluminum alloy described in the above scheme.
[0049] In the present application, the aluminum alloy product is specifically selected from seamless tubes for baseball bats.
[0050] The present application also provides a method for preparing an aluminum alloy product, comprising the following steps:
[0051] S1) melting the pure aluminum ingot according to the composition ratio, adding raw copper, raw zinc, raw magnesium and other master alloys, refining the obtained molten metal, and letting it stand;
[0052] S2) sequentially performing online degassing, online filtering and online adding of a grain refiner on the molten metal after standing, and obtaining an ingot after casting;
[0053] S3) subjecting the ingot to a three-stage homogenization treatment, wherein the first stage temperature of the three-stage homogenization treatment is 390-410° C., the second stage temperature is 450-470° C., and the third stage temperature is 470-475° C.;
[0054] S4) extruding the homogenized ingot, and then performing solid solution quenching and aging treatment.
[0055] In the preparation method of the aluminum alloy provided in the present application, the aluminum alloy is firstly smelted and cast to obtain an aluminum alloy ingot; the method specifically comprises the following steps:
[0056] 1) Add pure aluminum ingots to a smelting furnace and heat to melt. When the metal temperature rises to 720-760°C, add copper plates, zinc ingots, magnesium ingots and master alloys; then transfer the obtained molten metal to a holding furnace for refining. The refining time is not less than 15 minutes. The refined rare earth aluminum alloy molten metal is allowed to stand at 730-745°C for 30-60 minutes;
[0057] 2) The molten metal after standing is degassed and purified by an online argon degassing system, and then filtered online by a two-stage plate filter, and the filter plate precision is 40ppi and 50ppi; then the molten metal is introduced into a flow trough, and Al-5Ti-1B monofilament is continuously and evenly added, and cast into a round ingot by direct water-cooled semi-continuous casting, and the grain size grade of the round ingot is controlled to reach or exceed grade 1.
[0058] In the above step 1), electromagnetic stirring is started before the molten metal is transferred, and the stirring time is ≥30 min; refining agent is added during the refining process, and manual stirring and slag removal are performed after refining.
[0059] In the above step 2), in addition to adding grain refiner online, short Al-5Ti-1B wire is added at the inlet of the degassing box before casting to ensure the grain size grade of the round ingot; the hydrogen content in the aluminum liquid after online degassing and filtration is ≤0.12ml / 100gAl, and the slag content is ≤0.15mm 2 / kgAl to reduce defects such as pores and slag inclusions in the ingot.
[0060] The present application then subjects the obtained ingot to a three-stage homogenization treatment, wherein the first-stage temperature of the three-stage homogenization treatment is 390-410°C, the holding time is 8-12h, the second-stage temperature is 450-470°C, the holding time is 6-10h, and the third-stage temperature is 470-475°C, the holding time is 26-30h; specifically, the first-stage temperature is 400-408°C, the holding time is 8-10h, the second-stage temperature is 450-460°C, the holding time is 8-10h, and the third-stage temperature is 470-473°C, the holding time is 28-30h.
[0061] According to the present invention, the ingot after homogenization treatment is then sawed and milled before extrusion; the extrusion adopts medium-high temperature and low-speed forward piercing extrusion to prepare a seamless pipe, the medium-high temperature and low-speed forward piercing extrusion temperature is controlled to be 410-460°C, the extrusion speed is 0.1-0.5mm / s, the extrusion outlet temperature is controlled to be 370-390°C, and cooling is performed at room temperature; specifically, the forward piercing extrusion temperature is 440-450°C, the extrusion speed is 0.3-0.4mm / s, and the extrusion outlet temperature is 380-385°C.
[0062] In this application, the extruded pipe is finally subjected to solution quenching and artificial aging. The solution temperature of the solution quenching is 470-480°C, the holding time is 2-8h, the water temperature of the quenching is 20-30°C, the temperature of the aging treatment is 100-150°C, and the time is 12-24h; specifically, the solution temperature of the solution quenching is 470-475°C, the holding time is 3-5h, the water temperature of the quenching is 20-30°C, the temperature of the aging treatment is 120-140°C, and the time is 18-24h.
[0063] The present invention provides an ultra-high strength rare earth aluminum alloy, which promotes the precipitation of zinc, magnesium and copper elements from a matrix to form an η' strengthening phase by adding a large amount of main alloying elements such as zinc, magnesium and copper, and combines solid solution and artificial aging treatment, so that the tensile strength and yield strength of the rare earth aluminum alloy seamless pipe are relatively high; through rare earth scandium and zirconium composite microalloying and three-level homogenization treatment, a large amount of uniformly dispersed L12 type Al3 (Sc, Zr) phases are formed, which inhibit recrystallization and ensure that the fibrous extrusion structure of the pipe can be retained after solid solution treatment, thereby improving the strength and elongation of the alloy; in addition, the present invention adopts a medium-high temperature and low-speed perforation extrusion process, and successfully prepares a high-alloyed ultra-high strength aluminum alloy seamless pipe by increasing the extrusion temperature and reducing the extrusion speed.
[0064] In summary, the ultra-high strength rare earth aluminum alloy provided by the present invention is ultra-high alloyed with zinc, magnesium and copper elements and composite micro-alloyed with rare earth scandium and zirconium, and combined with a three-stage homogenization treatment to obtain a large amount of uniformly dispersed L12 type Al3 (Sc, Zr) phase; then, seamless pipes are prepared by extrusion; finally, a large amount of fine and uniformly dispersed precipitation phases are precipitated through solid solution and artificial aging, and at the same time, due to the pinning effect of the Al3 (Sc, Zr) phase, the fibrous extrusion structure of the pipe is retained, and the tensile strength of the ultra-high strength rare earth aluminum alloy pipe finally prepared reaches 700-790MPa, the yield strength is ≥660MPa, and the elongation is ≥8.0%.
[0065] In order to further understand the present invention, the ultra-high strength rare earth aluminum alloy and the preparation method thereof provided by the present invention are described in detail below in conjunction with the embodiments. The protection scope of the present invention is not limited by the following embodiments.
[0066] Example 1
[0067] The invention discloses an ultra-high strength rare earth aluminum alloy seamless pipe, wherein the mass percentage of each chemical component is as follows: silicon 0.025%, iron 0.074%, copper 1.72%, magnesium 1.85%, zinc 8.61%, manganese 0.42%, zirconium 0.08%, scandium 0.040%, titanium 0.03%, and the balance is Al.
[0068] The production method of the ultra-high strength rare earth aluminum alloy seamless pipe comprises the following steps:
[0069] 1) Add pure aluminum ingots into a smelting furnace and heat to melt. When the metal temperature rises to 743°C, add copper plates, zinc ingots, magnesium ingots and master alloys. Then transfer the molten metal to a holding furnace for refining for 26 minutes. The refined rare earth aluminum alloy molten metal is left to stand at 740°C for 38 minutes.
[0070] 2) After standing, the molten metal is degassed and purified by an online argon degassing system, and then filtered through a two-stage ceramic plate filter box with a primary filtration of 40ppi and a secondary filtration of 50ppi; the molten metal is then introduced into the launder, and the hydrogen content in the aluminum liquid in the launder is measured to be 0.11ml / 100gAl, and the slag content is 0.13mm 2 / kgAl, and continuously and evenly adding Al-5Ti-1B monofilaments, and casting into round ingots by direct water-cooling semi-continuous casting, wherein the grain size grade of the round ingot is grade 1;
[0071] 3) subjecting the round ingot to three-stage homogenization treatment: the first stage is 400° C. for 8 hours, the second stage is 450° C. for 10 hours, and the third stage is 470° C. for 30 hours;
[0072] 4) After the homogenized round ingot is sawed and milled, it is extruded by medium-high temperature and low speed forward piercing to form a seamless pipe with an outer diameter of 60 mm and a wall thickness of 4.5 mm. The medium-high temperature and low speed forward piercing extrusion temperature is 440° C., the extrusion speed is 0.3 mm / s, the seamless pipe extrusion outlet temperature is 382° C., and it is cooled at room temperature;
[0073] 5) The extruded seamless pipe is subjected to solution quenching and artificial aging treatment, wherein the solution quenching process is a solution temperature of 470° C. for 5 hours, room temperature water quenching, and the artificial aging process is a temperature of 120° C. for 24 hours.
[0074] According to tests, the rare earth aluminum alloy seamless pipe has a tensile strength of 708 MPa, a yield strength of 661 MPa, and an elongation after fracture of 11.5%.
[0075] Example 2
[0076] The preparation method for producing a rare earth aluminum alloy seamless pipe in Example 2 is substantially the same as that in Example 1, except that: the mass percentage of the chemical composition of the ultra-high strength rare earth aluminum alloy is: silicon 0.026%, iron 0.084%, copper 1.85%, magnesium 2.21%, zinc 8.94%, manganese 0.39%, zirconium 0.10%, scandium 0.042%, titanium 0.03%, and the balance is Al;
[0077] According to tests, the rare earth aluminum alloy seamless pipe has a tensile strength of 726 MPa, a yield strength of 669 MPa, and an elongation after fracture of 10.5%.
[0078] Example 3
[0079] The preparation method for producing a rare earth aluminum alloy seamless pipe in Example 3 is substantially the same as that in Example 1, except that: the mass percentage of the chemical composition of the ultra-high strength rare earth aluminum alloy is: silicon 0.030%, iron 0.091%, copper 2.06%, magnesium 2.49%, zinc 9.62%, manganese 0.41%, zirconium 0.11%, scandium 0.038%, titanium 0.03%, and the balance is Al;
[0080] According to tests, the rare earth aluminum alloy seamless pipe has a tensile strength of 759 MPa, a yield strength of 682 MPa, and an elongation after fracture of 9.0%.
[0081] Example 4
[0082] The preparation method for producing a rare earth aluminum alloy seamless pipe in Example 4 is substantially the same as that in Example 1, except that: the mass percentage of the chemical composition of the ultra-high strength rare earth aluminum alloy is: silicon 0.029%, iron 0.073%, copper 2.36%, magnesium 2.67%, zinc 9.95%, manganese 0.39%, zirconium 0.11%, scandium 0.041%, titanium 0.03%, and the balance is Al;
[0083] According to tests, the rare earth aluminum alloy seamless pipe has a tensile strength of 778 MPa, a yield strength of 709 MPa, and an elongation after fracture of 8.0%.
[0084] Example 5
[0085] The preparation method for producing the rare earth aluminum alloy seamless pipe in Example 5 is substantially the same as that in Example 4, except that: the mass percentage of the chemical composition of the ultra-high strength rare earth aluminum alloy is: silicon 0.032%, iron 0.069%, copper 2.28%, magnesium 2.65%, zinc 9.89%, manganese 0.40%, zirconium 0.10%, scandium 0.072%, titanium 0.03%, and the balance is Al;
[0086] According to tests, the rare earth aluminum alloy seamless pipe has a tensile strength of 786 MPa, a yield strength of 734 MPa, and an elongation after fracture of 9.0%.
[0087] Figure 1 is a surface grain structure photograph of the extruded seamless pipe of this embodiment; Figure 1 It can be seen that the surface of the extruded seamless pipe obtained by the above preparation method has no coarse-grained layer.
[0088] Figure 2 is a photo of the fibrous extruded grain structure of the core of the extruded seamless pipe of this embodiment; Figure 2 It can be seen that the core of the extruded seamless pipe obtained by the above preparation method has not undergone recrystallization, and the grain structure is mainly a fibrous extruded grain structure.
[0089] Figure 3 is a photo of the fibrous extruded grain structure of the core of the aged seamless pipe of this embodiment; Figure 3 It can be seen that after solution treatment, the core of the tube still retains the characteristics of fibrous extruded grain structure, and no recrystallized grain structure is observed.
[0090] Example 6
[0091] The alloy composition in Example 6 is substantially the same as that in Example 5, except that in step 4), when the seamless pipe is extruded by forward piercing, the extrusion temperature is 418°C, the extrusion speed is 0.1 mm / s, the seamless pipe extrusion outlet temperature is 385°C, and the pipe is cooled at room temperature; compared with Example 5, the extrusion speed is reduced to 0.1 mm / s.
[0092] According to tests, the rare earth aluminum alloy seamless pipe has a tensile strength of 778 MPa, a yield strength of 724 MPa, and an elongation after fracture of 9.0%.
[0093] Comparative Example 1
[0094] The preparation method for producing the rare earth aluminum alloy seamless pipe in Comparative Example 1 is substantially the same as that in Example 5, except that: the mass percentage of the chemical composition of the ultra-high strength aluminum alloy is: silicon 0.030%, iron 0.071%, copper 2.22%, magnesium 2.67%, zinc 9.92%, manganese 0.38%, zirconium 0.09%, scandium 0.001%, titanium 0.04%, and the balance is Al;
[0095] After testing, the tensile strength of the seamless pipe made of aluminum alloy is 779MPa, the yield strength is 702MPa, and the elongation after fracture is only 4.0%.
[0096] Figure 4 This is a photo of the recrystallized structure of the core of the aged seamless pipe of this comparative example; Figure 4 It can be seen that after solution aging treatment, coarse recrystallized grain structure was observed in some parts of the core of the pipe, indicating that obvious recrystallization occurred in the pipe.
[0097] Comparative Example 2
[0098] The alloy composition in Comparative Example 2 is substantially the same as that in Example 5, except that: in step 3), the first stage of homogenization treatment is 450° C. for 10 hours, and the second stage is 470° C. for 30 hours;
[0099] After testing, the tensile strength of the seamless pipe made of aluminum alloy is 758MPa, the yield strength is 679MPa, and the elongation after fracture is only 7.0%.
[0100] Comparative Example 3
[0101] The alloy composition of Comparative Example 3 is substantially the same as that of Example 5, except that in step 4), when the seamless pipe is extruded by forward piercing, the extrusion temperature is set at 435° C. and the extrusion speed is set at 2.0 mm / s.
[0102] Compared with Example 5, the extrusion speed was increased to 2.0 mm / s, which was not within the range of the present invention, and cracks appeared on the surface of the tube. Figure 5 This is a photo of the surface cracking of the extruded seamless pipe in this comparative example.
[0103] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
[0104] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. An ultra-high strength rare earth aluminum alloy, comprising, by mass percentage: Si≤0.1%; Fe≤0.1%; Ti≤0.05%; The balance is Al.
2. The ultra-high strength rare earth aluminum alloy according to claim 1, characterized in that: The content of Cu is 1.7-2.2%; and / or the content of Mg is 2.0-2.4%; and / or the content of Zn is 8.9-9.8%.
3. The ultra-high strength rare earth aluminum alloy according to claim 1, characterized in that: The content of Mn is 0.39-0.60%; and / or the content of Zr is 0.08-0.11%; and / or the content of Sc is 0.035-0.060%.
4. An aluminum alloy product, prepared from the aluminum alloy according to any one of claims 1 to 3.
5. The aluminum alloy product according to claim 4, characterized in that: The aluminum alloy product is a seamless tube for baseball bats.
6. The method for preparing the aluminum alloy product according to claim 4, comprising the following steps: S1) melting the pure aluminum ingot according to the composition ratio, adding raw copper, raw zinc, raw magnesium and other master alloys, refining the obtained molten metal, and letting it stand; S2) sequentially performing online degassing, online filtering and online adding of a grain refiner on the molten metal after standing, and obtaining an ingot after casting; S3) performing a three-stage homogenization treatment on the ingot, wherein the first stage temperature of the three-stage homogenization treatment is 390-410° C., the second stage temperature is 450-470° C., and the third stage temperature is 470-475° C.; S4) extruding the homogenized ingot, and then performing solid solution quenching and aging treatment.
7. The preparation method according to claim 6, characterized in that: The grain refiner is Al-5Ti-1B wire.
8. The preparation method according to claim 6, characterized in that: The insulation time of the first stage is 8 to 12 hours, the insulation time of the second stage is 6 to 10 hours, and the insulation time of the third stage is 26 to 30 hours.
9. The preparation method according to claim 6, characterized in that: The inlet temperature of the extrusion is 410-460°C, the extrusion speed is 0.1-0.5 mm / s, and the outlet temperature of the extrusion is 370-390°C.
10. The preparation method according to claim 6, characterized in that: The solution temperature of the solution quenching is 470-480°C, the holding time is 2-8h, the water temperature of the quenching is 20-30°C, the temperature of the aging treatment is 100-150°C, and the time is 12-24h.
Citation Information
Cited By
Al-Cu series welding wire and preparation method and application thereof
CN122299243A